The Decline in Access to Correspondent Banking Services in Emerging Markets : Trends, Impacts, and Solutions - World Bank Group (World Bank, Washington, DC, 2018)
To move funds internationally, banks rely on correspondent banking relationships (CBRs), roughly defined as the provision of banking services by one bank (the correspondent) to another bank (the respondent). CBRs are essential to international payments and provide an essential nexus between local economies and jurisdictions and the international financial system. They underpin international trade, remittances, and humanitarian financial flows among countries and are therefore particularly relevant to developing countries to support economic growth and development. Since the global financial crisis of 2008, global banks have been reviewing their CBRs and many have decided to terminate or limit their correspondent banking services (also known as derisking) to different regions, jurisdictions, or categories of clients.